2010
DOI: 10.1097/sla.0b013e3181e45b66
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Colorectal Surgery Produces Better Outcomes for High Risk Cancer Patients Compared to Open Surgery

Abstract: Laparoscopic resection of colorectal cancer can achieve excellent results even in "high risk" patients and is associated with significant reductions in length of stay compared with open resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
67
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 47 publications
7
67
0
4
Order By: Relevance
“…Despite these limitations, the current observations indicate that SLS has equivalent short-term surgical outcomes to MLS and is oncologically feasible in elderly patients, consistently with the results of previous reports in the general population (16)(17)(18)(19)(20)(21)(22)(23). Thus, we believe that these results justify the use of SLS in the routine treatment of elderly patients with colon cancer.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Despite these limitations, the current observations indicate that SLS has equivalent short-term surgical outcomes to MLS and is oncologically feasible in elderly patients, consistently with the results of previous reports in the general population (16)(17)(18)(19)(20)(21)(22)(23). Thus, we believe that these results justify the use of SLS in the routine treatment of elderly patients with colon cancer.…”
Section: Discussionsupporting
confidence: 80%
“…Several studies have reported that MLS demonstrates oncological results and surgical outcomes comparable to that of open surgery (16)(17)(18)(19)(20)(21)(22)(23). However, in the elderly, although MLS is reported to be non-inferior to the open procedure and may be an acceptable alternative in elderly patients with colorectal cancer (24), no study has investigated the feasibility of SLS in elderly patients with colon cancer, with the exception of one small study (10).…”
Section: Introductionmentioning
confidence: 99%
“…Clips or vascular staplers were used for mobilization, isolation, and ligation of the main vessels from the medial to the lateral aspect of colorectal tissues (Mehmood et al, 2011). As previously described, total mesorectal excision was performed using monopolar diathermy for rectal cancers (Heald et al, 1982;Hemandas et al, 2010). A wound protector was used to protect the sample extraction site, and anastomoses were performed intracorporeally.…”
Section: Surgical Techniquementioning
confidence: 99%
“…As previously described (Hemandas et al, 2010), open colectomy was performed using a midline incision, while laparoscopy was performed using a 5-port technique and a transverse incision of approximately 5 cm for extraction of the specimen. Patients were placed in the improved lithotomy position (Sachs and Peters, 1999) with the surgeon standing on the right side of the patient.…”
Section: Surgical Techniquementioning
confidence: 99%
“…In another study [6], while The United States Association of Colorectal Surgeons did not encourage laparoscopy, in other countries this procedure is found safe and comparable with open surgery regarding relapses and 3 years survival. Laparoscopy was found superior in high risk patients (in a study over 424 cases [7]) and also in reducing postoperative blood loss, low incidence of intestinal obstruction by adhesions and reduced long term morbidity compared with classic surgery in 1544 cases, without significant changes in local or distant relapses [8].…”
Section: Introductionmentioning
confidence: 99%